Moses Stuart and the Unintentional Secularization of American Biblical Studies - Lundeen, Erik (Harvard theological review, 2023)
Building off recent work investigating the development of modern biblical criticism, this essay argues that the broadly conservative scholar Moses Stuart (1780-1852) should be seen as playing a key but unintentional role in the secularization of biblical studies in nineteenth-century America. Stuart played this role in several ways. Hermeneutically, he imbibed and popularized naturalistic assumptions summed up in the maxim that the Bible should be interpreted like any other book. Educationally, when arguing for the curricular importance of Hebrew studies, he justified the Bible’s importance not via its role as Scripture, but primarily via its place as excellent classical literature. Stuart’s example thereby suggests that, in studying the demise of Scripture’s sacred status in the modern era, scholars must pay attention not only to the attacks of the Bible’s liberal critics but also to the methods and assumptions of its conservative defenders.